The Influence of The Culinary Tiktok Account @Solofoodie on The Culinary Tourism Interest of Followers - Dita, Melfia Salsa; Santoso, Budi (Universitas Syiah Kuala, 2025)
This study examines the influence of exposure to the TikTok culinary account @solofoodie on followers' interest in culinary tourism. The research employed a quantitative approach with a causal inferential design. The sample consisted of 100 active followers of the @solofoodie TikTok account, selected using the Taro Yamane formula. Data were collected through an online Likert scale questionnaire and analyzed using simple linear regression. The results indicated a positive and statistically significant effect of TikTok exposure on culinary tourism interest, with an R value of 0.746 and a significance level of 0.001. The regression model obtained was Y = 0.592 + 1.131X, indicating that each additional point in TikTok exposure increases culinary interest by 1.131 points. These findings confirm that culinary content on TikTok can shape audience preferences and behavioral intentions, strengthening the relevance of the Stimulus-Organism-Response (S-O-R) theory in social media